2019
DOI: 10.4103/ijmr.ijmr_672_18
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of the cytotoxic effects of statins on U266 myeloma cell line

Abstract: Background & objectives: Statins are one of the most widely used drugs and have antilipidemic effects as well as antioxidant, anti-inflammatory, anti-angiogenic and anti-tumorigenic effects. It has been shown that the synergistic combinations of statins which can provide better clinical benefit in the treatment of cancer and if administered with other anticancer agents, may be an alternative treatment modality. The aim of this study was to assess the efficacy of administrating statin in multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In vivo studies evidenced that statins reduce tumor growth and arrest metastasis progression ( 113 , 182 186 ). Terzi and co-workers ( 187 ) evaluated the effect of two statins, atorvastatin and simvastatin, combined with the standard chemotherapeutic agent, bortezomib, in human multiple myeloma. The results showed that statins are able to improve the effectiveness of bortezomib and reduce the adverse effects ( 187 ).…”
Section: Cholesterol Metabolic Reprogramming In Cancer: Pharmacological Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies evidenced that statins reduce tumor growth and arrest metastasis progression ( 113 , 182 186 ). Terzi and co-workers ( 187 ) evaluated the effect of two statins, atorvastatin and simvastatin, combined with the standard chemotherapeutic agent, bortezomib, in human multiple myeloma. The results showed that statins are able to improve the effectiveness of bortezomib and reduce the adverse effects ( 187 ).…”
Section: Cholesterol Metabolic Reprogramming In Cancer: Pharmacological Targetingmentioning
confidence: 99%
“…Terzi and co-workers ( 187 ) evaluated the effect of two statins, atorvastatin and simvastatin, combined with the standard chemotherapeutic agent, bortezomib, in human multiple myeloma. The results showed that statins are able to improve the effectiveness of bortezomib and reduce the adverse effects ( 187 ). The combined treatment of pivastatin with gemcitabine synergically reduced cell proliferation of MIA PaCa-2 cells inducing cell cycle arrest.…”
Section: Cholesterol Metabolic Reprogramming In Cancer: Pharmacological Targetingmentioning
confidence: 99%
“…To date, few studies have evaluated statins in combination with bortezomib in MM [14,53]. Notably, our study is the first to describe a molecular subtype of MM in which these two drugs interact synergistically, at physiologically relevant concentrations.…”
Section: Discussionmentioning
confidence: 84%
“…Myeloma cells were reported to need cholesterol for growth and proliferation in mouse cell lines. In addition, drugs such as simvastatin, atorvastatin, and lovastatin were shown to cause the death of MM cell lines [4,5]. Failure to fully evaluate microenvironment effects was one of the limitations of these studies.…”
Section: Discussionmentioning
confidence: 99%